Trendi razvoja olimpijskega teka na 100 metrov - Filipič, Jan (Šport (Ljubljana), 2018)
The aim of the research is to analyse the trends of the Olympic Games' 100-meter sprint from the last 28 years. Within the framework of the present graduation thesis, the changes in the following fields were established: the results of the 100-meter sprint, the age of the athletes, some morphological variables of the competitors, the reaction times and the gender differences were compared. Comprised within the research, which is gathered online, is the data analysis of the 128 male and female sprinters who participated in the final 100-meter sprint events at the Olympic Games between 1984 and 2012. The data was statistically processed utilizing IBM SPSS Statistics 20 software. In order to determine the gender differences, an ANOVA was used. According to the results of the analysis, the developmental trends of the Olympic's 100-meter sprint are changing differently for both female and male competitors. The sprinters of different ages and morphological characteristics are achieving top results with extremely small differences.
Keywords: morfološke spremenljivke; olimpijske igre; razvoj; reakcijski čas; šport; šprint; tek na 100 metrov